2014
DOI: 10.1073/pnas.1323277111
|View full text |Cite
|
Sign up to set email alerts
|

Mobile hydrogen carbonate acts as proton acceptor in photosynthetic water oxidation

Abstract: Cyanobacteria, algae, and plants oxidize water to the O 2 we breathe, and consume CO 2 during the synthesis of biomass. Although these vital processes are functionally and structurally well separated in photosynthetic organisms, there is a long-debated role for CO 2 /HCO − 3 in water oxidation. Using membrane-inlet mass spectrometry we demonstrate that HCO − 3 acts as a mobile proton acceptor that helps to transport the protons produced inside of photosystem II by water oxidation out into the chloroplast's lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
59
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 46 publications
10
59
0
5
Order By: Relevance
“…A role of HCO 3 − in photoassembly of the cluster has been suggested previously, and remains possible (5,16). A role of HCO 3 − , enhancing proton removal from the site of water splitting, was recently reported (10), and it was suggested that this could represent a regulatory link between CO 2 and water splitting (10). The present work also shows a mechanism in which the CO 2 level can control PSII activity (see below).…”
Section: Added (Triangles) (D) Effect Of Preillumination On Hco 3 − supporting
confidence: 78%
See 3 more Smart Citations
“…A role of HCO 3 − in photoassembly of the cluster has been suggested previously, and remains possible (5,16). A role of HCO 3 − , enhancing proton removal from the site of water splitting, was recently reported (10), and it was suggested that this could represent a regulatory link between CO 2 and water splitting (10). The present work also shows a mechanism in which the CO 2 level can control PSII activity (see below).…”
Section: Added (Triangles) (D) Effect Of Preillumination On Hco 3 − supporting
confidence: 78%
“…The "donor-side" studies of PSII are often based on the idea that the acceptor-side HCO 3 − has a single fixed binding constant for HCO 3 − bound to the Fe 2+ , keeping it permanently bound to PSII under physiological conditions (10). These results change that premise, and thus it may be worthwhile reassessing some phenomena attributed to the donor side.…”
Section: Added (Triangles) (D) Effect Of Preillumination On Hco 3 − mentioning
confidence: 99%
See 2 more Smart Citations
“…If proton removal is slow, this leads to less efficient O 2 production and consequently may lead to donor side photoinhibition (Minagawa et al, 1996). That HCO 3 -acts as a mobile proton carrier has been recently demonstrated for spinach (Spinacia oleracea) PSII membrane fragments using membrane inlet mass spectrometry (MIMS; Koroidov et al, 2014). These results show that PSII possesses a light-and HCO 3 --dependent CO 2 production for up to 50% of the O 2 produced.…”
mentioning
confidence: 97%